INSTITUTIONAL AND LEGAL ASPECTS OF ESTABLISHMENT AND DEVELOPMENT OF THE FINANCIAL MONITORING SYSTEM IN UKRAINE - Vovchak, Olha; Yendorenko , Lyubov (Socio-economic relations in the digital society, 2021)
The article analyzes the prerequisites of formation and development of financial monitoring in the banking sector of Ukraine. The purpose of the article is to reveal the essence of transformational changes in financial monitoring in the banking sector of Ukraine. study of institutional and legal preconditions for the formation and development of the financial monitoring system in Ukraine. Considerable attention is paid to the normative-legal basis, in particular, which acted from the beginning of the introduction of a national system for prevention and countering to legalization (laundering) of the proceeds of crime or terrorist financing and financing proliferation of weapons of mass destruction, and until today: these key changes in the current legislation in terms of risk-oriented approach, case reporting, threshold financial transaction, number of features that are subject to mandatory financial monitoring, subjects of state and primary financial monitoring are determined the main normative acts regulating or regulated financial monitoring in the banking sector are evaluated etc. It is based that an important and productive stage is the period since 2002, at that time, regulatory and legal regulation in the legislation of Ukraine was developed. The peculiarities of the creation and development of The State Financial Monitoring Service of Ukraine, the formation of the implementation of the Strategy on the prevention and counteraction to legalization (laundering) of the proceeds from crime, terrorist financing and financing of the proliferation of weapons of mass destruction for the period up to 2020. The influence of international legal acts/organizations, including FATF, MONEYVAL, Egmont Group, Directives (EU) and others, which applied their measures of influence Ukraine in the field of financial monitoring, this manner to improve the legislation on the territory of Ukraine. In general, financial monitoring of the banking sector of Ukraine has undergone significant changes since its inception. International organizations play an important role in financial monitoring, but the regulatory framework is crucial in ensuring proper financial monitoring. According to the analysis, the imperfect legal provision did not fully affect the efficiency of the system in the field of prevention and counteraction to legalization (laundering) of proceeds from crime, terrorist financing and financing of proliferation of weapons of mass destruction.
Keywords: financial monitoring; terrorism financing; financing of the proliferation of weapons of mass destruction; legalization (laundering) of income; anti-money laundering; banking sector; law